Legal and legitimate protection of agricultural-oriented land - Si Mohamed, Noui; El Kahina, Zouaoui (Journal of Human Sciences, 2023)
After the attacks on agricultural real estate which it is still subjected to by changing its direction and making it a container for industrial and residential real estate the Algerian legislator enacted a set of laws and instructions that would provide protection for this natural wealth that requires protection and special care. It is true that agricultural real estate is varieties and types. but the legislature he did not differentiate between land of high fertility and land of medium fertility. or land owned by the state. or land owned by the private. as the agricultural property remains agricultural and needs protection. Food for all people and regulate their continuation naturally.